108. Verification of skin dose values calculated by a dose tracking software using GAFCHROMIC films measurements. (December 2018) - Rottoli, F.; De Mattia, C.; Sutto, M.; Colombo, P.E.; Rampoldi, A.; Torresin, A.
Abstract : Purpose: To compare skin dose values and their spatial distribution obtained with the radiation dose tracking software with measurements on gafchromic films on phantom and patients. Methods: In NEXO[DOSE]® (Bracco, Milan) the distribution of skin dose of interventional radiology procedures is calculated on the surface of a mathematical torso phantom using exposure parameters of each irradiation event from the Radiation Dose Structured Report and additional angiography-specific information (table and mattress attenuation, KAP correction factor and tube position relative to the table). The skin dose map and the peak skin dose (PSD), i.e. the maximum cumulative dose value, are displayed in the software. To test the accuracy of the algorithm we irradiated GAFCHROMIC XR-RV3 films wrapped on a phantom with different test fields using a Philips Integris Allura FD20 angiography. Absolute dose values and geometric accuracy of the phantom dose map calculated by NEXO[DOSE]® were compared with the film. The tool was also clinically tested by placing a film on the patient's back during interventional embolization procedures at the beam entrance side. Results: In the phantom, the geometric accuracy calculated by NEXO[DOSE]® was within 10% (Fig. 1). the cumulative dose was in good agreement for high dose fields (<15%) where the deterministic effects are expected. Discrepancies increase in low dose regions of a procedure: the software does not account for the out-of-field scatter, which is more relevant in low dose area (Table 1 ). PSD agreement was within 15%. During clinical procedures, films confirmed that NEXO[DOSE]® can estimate the dose distribution on the patient's skin even for more complex irradiation geometries and calculated PSD differs less than 15% from the film value. Conclusions: NEXO[DOSE]® provides an estimation of the geometric distribution of skin dose and PSD within 15% and thus it can help in the dosimetric management of the procedures.